Language in Tourism: Linguistic Landscape Analysis of Candi Jiwa Museum Collections - Syafroni, Roni Nugraha; Pratama, Rizki Teja; Rosalinda, Rosalinda (Politeknik Negeri Bandung, 2025)
Heritage studies often struggle to move beyond descriptive cataloguing toward interpretive frameworks that reveal how artifacts encode cultural meaning. This study applies semantic field theory—originally developed for linguistics—to the collections of the Candi Jiwa Museum in West Java, Indonesia. Through qualitative analysis of artifacts and contextual materials, nine semantic domains were identified, including funerary ritual, architectural symbolism, environmental adaptation, domestic–sacred convergence, and symbolic economy. These findings demonstrate that artifacts function not as inert remnants but as interconnected semiotic systems that sustain continuity, cosmology, and identity values. The study advances two key contributions. Theoretically, it extends semantic field analysis into material culture, showing how objects can be decoded as networks of meaning without reducing their contextual richness. Practically, it repositions museums as pedagogical mediators that engage youth through interpretive dialogue rather than passive display. The results challenge conventional heritage discourse that privileges the authenticity of objects, arguing instead for preservation of semiotic systems as the true foundation of cultural sustainability.